2015
DOI: 10.1007/s40495-014-0001-y
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide DNA Methylation Profiling in Dietary Intervention Studies: a User’s Perspective

Abstract: Within the past decade, epigenetic mechanisms and their modulation by dietary agents have gained major interest in the cancer prevention and nutrition community. Gene expression is epigenetically regulated by DNA methylation, histone tail modifications, and non-coding (micro) RNAs. Given the fact that epigenetic aberrations are reversible and represent potentially initiating events in the development of diseases, they have been identified as promising new targets for prevention strategies. Evidence is accumula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 84 publications
(89 reference statements)
0
1
0
Order By: Relevance
“…23 Both of them cooperate to methylate the promoter regions of the OCT3/4 and Nanog genes during the differentiation of embryonic carcinoma cells and ES cells, and the removal of them can lead to insufficient methylation and disordered OCT3/4 expression. 24,25 Here, we demonstrated that in A549 and NCI-H226 lung cells the activity of the maintenance methyltransferase DNMT1 and DNMT3b decreased after 5-Fu/CDDP treatment, but DNMT3a in NCI-H226 cells significantly increased. DNMT3a was increased in the NCI-H226 cell line, which may be related to the interference of other factors in the NCI-H226 cell line.…”
Section: The Expression Of H3k9me3 and H3k9ace By Chipmentioning
confidence: 70%
“…23 Both of them cooperate to methylate the promoter regions of the OCT3/4 and Nanog genes during the differentiation of embryonic carcinoma cells and ES cells, and the removal of them can lead to insufficient methylation and disordered OCT3/4 expression. 24,25 Here, we demonstrated that in A549 and NCI-H226 lung cells the activity of the maintenance methyltransferase DNMT1 and DNMT3b decreased after 5-Fu/CDDP treatment, but DNMT3a in NCI-H226 cells significantly increased. DNMT3a was increased in the NCI-H226 cell line, which may be related to the interference of other factors in the NCI-H226 cell line.…”
Section: The Expression Of H3k9me3 and H3k9ace By Chipmentioning
confidence: 70%